Boys who have abused : psychoanalytic psychotherapy with victim/perpetrators of sexual abuse - Woods, John, 1948- (Forensic focus ;, 2003)
John Woods presents a theoretical approach and practical suggestions for mental health practitioners working therapeutically with young people who have abused. Drawing on his long-standing experience, he has developed an integrated theory that bridges the gap between existing cognitive behavioural and psychoanalytic approaches. He shows how this individual treatment model can be applied in a range of contexts including residential settings, group and family work, as well as in individual work. In-depth case studies throughout the book demonstrate how exploring the individual's whole life-cours.